2015
DOI: 10.1007/s10522-015-9625-5
|View full text |Cite
|
Sign up to set email alerts
|

Stratification of yeast cells during chronological aging by size points to the role of trehalose in cell vitality

Abstract: Cells of the budding yeast Saccharomyces cerevisiae undergo a process akin to differentiation during prolonged culture without medium replenishment. Various methods have been used to separate and determine the potential role and fate of the different cell species. We have stratified chronologically-aged yeast cultures into cells of different sizes, using centrifugal elutriation, and characterized these subpopulations physiologically. We distinguish two extreme cell types, very small (XS) and very large (L) cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 37 publications
2
19
0
Order By: Relevance
“…Second, we analyzed mitochondrial morphology and found that the ‘small sub-population’ was enriched in cells with globular mitochondria ( Figure 3B ). Thus, to some extent, we found more senescent cells among very small cells, in agreement with ( Svenkrtova et al, 2016 ). Accordingly, when cells were micro-manipulated on plate to individually test their re-proliferation capacities ( Laporte et al, 2011 ), small cells were less prone to form colonies than large cells ( Figure 3—figure supplement 1A ).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Second, we analyzed mitochondrial morphology and found that the ‘small sub-population’ was enriched in cells with globular mitochondria ( Figure 3B ). Thus, to some extent, we found more senescent cells among very small cells, in agreement with ( Svenkrtova et al, 2016 ). Accordingly, when cells were micro-manipulated on plate to individually test their re-proliferation capacities ( Laporte et al, 2011 ), small cells were less prone to form colonies than large cells ( Figure 3—figure supplement 1A ).…”
Section: Resultssupporting
confidence: 91%
“…Cell volume has been suggested to strongly influence non-proliferating cell survival. Yet while the Werner-Washburne laboratory found that only small daughter cells were quiescent ( Allen et al, 2006 ; Aragon et al, 2008 ; Werner-Washburne et al, 2012 ; Davidson et al, 2011 ), the Pichova lab reported that a sub-population composed of very small cells (2–4 µm in diameter) contained mostly senescent or dead cells ( Svenkrtova et al, 2016 ). To revisit these conflicting data, we measured the individual cell volume of WT cells expressing Ilv3-RFP grown in YPD, just after their deposition onto a YPD microscope pad.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, stationary phase populations have been separated into subpopulations according to cell size (Svenkrtova et al, 2016). It was found that, with time, very small cells (2 to 4 µm in diameter) displayed a reduced ability to re-proliferate (Svenkrtova et al, 2016). In agreement, at the population scale, we found that very small cells (less than 30 fl in volume, or ∼2.5 µm in diameter) have a slightly increased susceptibility to enter senescence.…”
Section: Cell Sizesupporting
confidence: 78%
“…Recently, stationary phase populations have been separated into subpopulations according to cell size (Svenkrtova et al, 2016). It was found that, with time, very small cells (2 to 4 µm in diameter) displayed a reduced ability to re-proliferate (Svenkrtova et al, 2016).…”
Section: Cell Sizementioning
confidence: 99%